2013
DOI: 10.1186/1471-2164-14-449
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary dynamics of copy number variation in pig genomes in the context of adaptation and domestication

Abstract: Background: Copy number variable regions (CNVRs) can result in drastic phenotypic differences and may therefore be subject to selection during domestication. Studying copy number variation in relation to domestication is highly relevant in pigs because of their very rich natural and domestication history that resulted in many different phenotypes. To investigate the evolutionary dynamic of CNVRs, we applied read depth method on next generation sequence data from 16 individuals, comprising wild boars and domest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
134
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 123 publications
(158 citation statements)
references
References 55 publications
22
134
2
Order By: Relevance
“…We also compared CNVRs in this study with previous pig CNV studies [24, 25, 35, 36, 39, 41, 42]. After merging the results of recent reports, a total of 849 out of 3,131 CNVRs (27.75%) with the length of 33.02 Mb in our study overlapped with those previously reported (see Table 4).…”
Section: Resultssupporting
confidence: 57%
“…We also compared CNVRs in this study with previous pig CNV studies [24, 25, 35, 36, 39, 41, 42]. After merging the results of recent reports, a total of 849 out of 3,131 CNVRs (27.75%) with the length of 33.02 Mb in our study overlapped with those previously reported (see Table 4).…”
Section: Resultssupporting
confidence: 57%
“…By mean of whole-genome resequencing, Rubin et al (2012) observed a reduced number of candidate regions with fixed or highfrequency nonsense mutations, leading to the conclusion that gene inactivation did not had an important role in the pig domestication and breeding processes. A similar pattern was found in regions containing copy number variants (Rubin et al, 2012; see also Paudel et al, 2013). Nevertheless, Rubin et al (2012) identified an excess of nonsynonymous-derived substitutions in domesticated pigs, a result that is expected if selective events predominate during and after domestication.…”
Section: Moving Towards An Autosomal and Paternal Marker-based Definimentioning
confidence: 56%
“…The KIT gene is a very well-known gene that is involved in coat colour [23]. European pigs contain a copy number variable dominant white allele, mostly in homozygous form [21,48]. We clearly see European haplotypes surrounding this gene rather than Asian, suggesting selection against introgression at this locus.…”
Section: (C) Pigmentation Genesmentioning
confidence: 75%